2007
DOI: 10.1016/j.jasms.2007.04.003
|View full text |Cite|
|
Sign up to set email alerts
|

A collision cross-section database of singly-charged peptide ions

Abstract: A database of ion-neutral collision cross-sections for singly-charged peptide ions is presented. The peptides included in the database were generated by enzymatic digestion of known proteins using three different enzymes, resulting in peptides that differ in terms of amino acid composition as well as N-terminal and C-terminal residues. The ion-neutral collision crosssections were measured using ion mobility (IM) spectrometry that is directly coupled to a time-of-flight (TOF) mass spectrometer. The ions were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
94
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 32 publications
0
94
0
Order By: Relevance
“…In repeated application of the algorithm to the same dataset, the resulting clustering very similar as measured by the adjusted Rand index [34]. is ϳ 5% larger than that expected for ions that fall on the globular mobility-mass trendlines [15], which suggests that the ion structures are somewhat elongated (partial helix). MD simulations as described above yield a total of 3600 candidate structures for the [M ϩ H] ϩ ions and 631 fall within Ϯ2% of ⍀ meas .…”
Section: Dynamic Clustering Algorithmmentioning
confidence: 87%
See 2 more Smart Citations
“…In repeated application of the algorithm to the same dataset, the resulting clustering very similar as measured by the adjusted Rand index [34]. is ϳ 5% larger than that expected for ions that fall on the globular mobility-mass trendlines [15], which suggests that the ion structures are somewhat elongated (partial helix). MD simulations as described above yield a total of 3600 candidate structures for the [M ϩ H] ϩ ions and 631 fall within Ϯ2% of ⍀ meas .…”
Section: Dynamic Clustering Algorithmmentioning
confidence: 87%
“…In previous work, we showed that a large proportion of singly charged peptide ions (formed by MALDI) appear on a single trendline in 2D mobility-m/z plots, i.e., plots of arrival-time distribution (ATD) or ion-neutral collision cross-section (⍀) versus m/z [15]; however, a few ion signals deviate (Ͼ3% to ϳ20%) from the expected trendline and nonpeptidic ion signals appear on separate, compound class specific trendlines [14,15]. Ruotolo et al showed that gas-phase [M ϩ H] ϩ ions of LLGNVLVVVLAR (derived from bovine hemoglobin) prefer extended (helical) structure(s) resulting in a larger collision cross-section than random coil structures having the same or similar m/z values [12,13], while some post-translationally modified (PTM) peptide ions (phosphopeptides) tend to pack more tightly than the unmodified protonated peptide ions owing to intra-molecular charge-solvation and/or formation of salt-bridged type structures [16,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that such proximity results from the formation of multiple electrostatic interactions between the peptide backbone and the site of protonation at arginine to yield a globular peptide structure, a common effect observed in gas-phase protonated peptide structures. [6][7] The present study derives advantage from this observation, informing a choice of model peptides to optimize reaction around the seventh residue.…”
Section: Frips (B) Shows Greater Selectivity In Dissociation Than Cidmentioning
confidence: 98%
“…It is likely that such proximity results from the formation of multiple electrostatic interactions between the peptide backbone and the site of protonation at arginine to yield a globular peptide structure, a common effect observed in gas-phase protonated peptide structures. [6][7] The present study derives advantage from this observation, informing a choice of model peptides to optimize reaction around the seventh residue.In contrast to the FRIPS products of the alanine model peptide, the FRIPS spectrum of AARAAMAHA in Figure S1b shows little CO 2 loss or backbone a ion formation at alanine residues and is instead dominated by dissociation at methionine and histidine. The formation of the a 8 ion through hydrogen atom abstraction at C β followed by β-cleavage of the backbone C α −C bond suggests a low activation energy for these processes at the histidine residue.…”
mentioning
confidence: 98%